Pengaruh Cash Turnover, Firm Size, Leverage, Dan Sales Growth Terhadap Profitabilitas (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to determine the effect of cash turnover, firm size, leverage,and sales growth on profitability in manufacturing companies listed on the IDX in 2017-2019. The sample was selected using purposive sampling method and valid data were 36companies. The data processing technique uses multiple regression analysis with the Eviews11 program and Microsoft Excel 2013. The results show that sales growth has a significantpositive effect on profitability, leverage has a significant negative effect on profitability,while cash turnover and firm size have a negative and insignificant effect on profitability.The implication of this research is the need to increase profitability for the survival of thecompany which is influenced by increased sales growth and leverage to expand its businessso that it can provide good signals for investors.